Slurry for non-aqueous battery electrodes, and method for producing non-aqueous battery electrodes and non-aqueous batteries
Patent Information
- Application Number
- JP2023096498
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-02-09
- Filing Date
- 2023-06-12
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2039-01-31
AI Technical Summary
【0011】 本発明の非水系電池電極用スラリーを用いることより、スラリーを厚塗りし、電極活物質層を厚く形成してもクラックが入りにくい電極を得ることができる。
Smart Images

Figure 0007632520000001 
Figure 0007632520000002 
Figure 0007632520000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a slurry for a non-aqueous battery electrode, and a method for producing a non-aqueous battery electrode and a non-aqueous battery. This application claims priority based on Japanese Patent Application No. 2018-022334, filed on February 9, 2018, the contents of which are incorporated herein by reference. [Background technology]
[0002] 2. Description of the Related Art In recent years, non-aqueous lithium ion batteries have been attracting attention from the viewpoint of miniaturization and weight reduction in electronic devices such as notebook computers, communication devices such as mobile phones, and power tools.
[0003] The lithium ion non-aqueous battery includes a positive electrode using a metal oxide such as lithium cobalt oxide as an active material, a negative electrode using a carbon material such as graphite as an active material, and an electrolyte solvent mainly consisting of carbonates. In the lithium ion non-aqueous battery, the battery is charged and discharged by the movement of lithium ions between the positive electrode and the negative electrode. The positive electrode can be obtained by forming a positive electrode layer from a composition containing a positive electrode active material such as a metal oxide and a binder on the surface of a positive electrode current collector such as aluminum foil. The negative electrode can be obtained by forming a negative electrode layer from a composition containing a negative electrode active material such as graphite and a binder on the surface of a negative electrode current collector such as copper foil. Therefore, each binder has the role of binding the active material and the binder to prevent cohesive failure of the positive electrode layer and the negative electrode layer.
[0004] As a binder, polyvinylidene fluoride (PVDF)-based binders using organic solvent-based N-methylpyrrolidin-2-one (NMP) as a solvent are well known (see, for example, Patent Document 1). However, this binder has low binding properties between active materials and between active materials and current collectors, and requires a large amount of binder for practical use, resulting in a decrease in the capacity of non-aqueous batteries. In addition, since NMP, an expensive organic solvent, is used as the binder, there are problems with the price of the final product and the preservation of the working environment during the preparation of the slurry or current collector.
[0005] As a method for solving these problems, development of water-dispersed binders has been underway. For example, water dispersions of styrene-butadiene rubber (SBR) that use carboxymethyl cellulose (CMC) as a thickener are known (see, for example, Patent Documents 2 to 4). In addition, Patent Document 5 proposes a water-dispersed binder used in electrodes of secondary batteries that is obtained by emulsion polymerization of an ethylenically unsaturated monomer containing styrene, an ethylenically unsaturated carboxylic acid ester monomer, an ethylenically unsaturated carboxylic acid monomer, and an internal crosslinking agent in the presence of a surfactant. These are inexpensive because they are aqueous dispersions, which is advantageous from the viewpoint of protecting the working environment. In addition, because they have relatively good adhesion between the active materials themselves and between the active materials and the current collector, they can be used in smaller quantities than PVDF-based binders to produce electrodes, which has the advantage of enabling non-aqueous batteries to have higher output and capacity.
[0006] Recently, from the viewpoint of environmental friendliness, there has been a strong demand for non-aqueous lithium ion batteries, particularly those with high voltage, high capacity and high energy density, as non-aqueous batteries for electric vehicles or hybrid vehicles. As a countermeasure against these problems, there is a method of coating the electrode current collector with a thick slurry to form a thick electrode active material layer. However, if the electrode is applied too thickly, cracks tend to form in the electrode, and the battery performance is not necessarily good. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-298386 [Patent Document 2] Japanese Patent Application Publication No. 5-74461 [Patent Document 3] Japanese Patent Application Publication No. 8-250123 [Patent Document 4] JP 2011-204573 A [Patent Document 5] JP 2011-243464 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to solve the problems of the conventional technology and to provide a slurry for non-aqueous battery electrodes which is an aqueous dispersion system, has good adhesion between active materials and between the active materials and the current collector, is less likely to crack even when applied thickly, and the active materials are less likely to peel off from the current collector surface, and to provide a method for manufacturing a non-aqueous battery electrode and a non-aqueous battery which use the slurry. [Means for solving the problem]
[0009] The present inventors conducted extensive research to solve the above problems, and discovered that the occurrence of cracks can be prevented by adding a specific organic solvent as a crack inhibitor to an aqueous dispersion slurry, thereby solving the above problems. That is, the present invention includes the following aspects.
[0010] [1] A slurry for a non-aqueous battery electrode comprising an active material for a non-aqueous battery electrode (A), a binder resin (B), a crack inhibitor (C), and water, The non-aqueous battery electrode slurry is characterized in that the crack prevention agent (C) has a boiling point of 120°C or higher at 1 atmospheric pressure and a solubility in water at 20°C of 10 g / 100 mL or higher. [2] The nonaqueous battery electrode slurry according to [1], wherein the crack inhibitor (C) is at least one selected from the group consisting of N-methylpyrrolidin-2-one, ethylene glycol, diethylene glycol, ethylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, N,N-dimethylformamide, and dimethyl sulfoxide. [3] The slurry for a nonaqueous battery electrode according to [1], wherein the crack inhibitor (C) is an organic solvent having a boiling point of 150° C. or higher at 1 atmospheric pressure. [4] The slurry for a non-aqueous battery electrode according to claim 1, wherein the crack prevention agent (C) is an organic solvent having a boiling point of more than 200°C at 1 atmospheric pressure. [5] The slurry for a non-aqueous battery electrode according to any one of [1] to [4], comprising 10 to 500 parts by mass of the crack inhibitor (C) per 100 parts by mass of the binder resin (B). [6] The slurry for a nonaqueous battery electrode according to any one of [1] to [5], further comprising a thickener (D). [7] The slurry for a nonaqueous battery electrode according to [6], wherein the thickener (D) is carboxymethyl cellulose (CMC). [8] The slurry for a non-aqueous battery electrode according to any one of [1] to [7], wherein the binder resin (B) is at least one selected from the group consisting of a copolymer of a styrene-based monomer and a diene-based monomer, and a copolymer of a styrene-based monomer and an ethylenically unsaturated carboxylic acid ester monomer. [9] The slurry for a nonaqueous battery electrode according to any one of [1] to [8], wherein the binder resin (B) contains a copolymer of a styrene-based monomer and a diene-based monomer, and the styrene-based monomer component accounts for 5 to 70 mass% of the total ethylenically unsaturated monomer components constituting the copolymer, and the diene-based monomer component accounts for 30 to 95 mass%.
[10] The slurry for a nonaqueous battery electrode according to any one of [1] to [9], wherein the binder resin (B) contains a copolymer of a styrene-based monomer and an ethylenically unsaturated carboxylic acid ester monomer.
[11] The slurry for a non-aqueous battery electrode according to any one of [1] to
[10] , wherein the binder resin (B) contains a copolymer of a styrene-based monomer, an ethylenically unsaturated carboxylic acid ester monomer, and an ethylenically unsaturated carboxylic acid monomer.
[12] The amount of styrene used in the binder resin (B) is 10 to 70 mass% of the total ethylenically unsaturated monomer components forming the copolymer, the amount of the ethylenically unsaturated carboxylic acid ester monomer used is 25 to 85 mass % of the total ethylenically unsaturated monomer components forming the copolymer, The slurry for a non-aqueous battery electrode according to
[11] , wherein the amount of the ethylenically unsaturated carboxylic acid monomer used is 0.01 to 10 mass % of the total ethylenically unsaturated monomer components forming the copolymer.
[13] A method for producing a nonaqueous battery electrode, comprising the steps of applying the slurry according to any one of [1] to
[12] onto a current collector and curing the slurry.
[14] A method for producing a non-aqueous battery, comprising the step of producing a non-aqueous battery electrode according to
[13] . Effect of the Invention
[0011] By using the non-aqueous battery electrode slurry of the present invention, it is possible to obtain an electrode that is resistant to cracks even when the slurry is applied thickly and a thick electrode active material layer is formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Non-aqueous battery electrode slurry) The non-aqueous battery electrode slurry of the present invention contains an active material (A), a binder resin (B), a crack inhibitor (C), and water as essential components. The crack inhibitor (C) has a boiling point of 120° C. or higher at 1 atmosphere and a solubility in water of 10 g / 100 mL or higher at 20° C. The slurry may further contain a thickener (D). In this specification, "(meth)acrylic" is a general term for acrylic and methacrylic, and "(meth)acrylate" is a general term for acrylate and methacrylate.
[0013] [Active material (A)] The slurry for a non-aqueous battery electrode of the present invention contains an active material (A) as an essential component. The active material used in the present invention may be a positive electrode active material or a negative electrode active material. In the slurry for a non-aqueous battery electrode of one embodiment of the present invention, the active material (A) is a negative electrode active material. When a negative electrode active material is used as the active material (A), the effect is easily exhibited. The shape of the active material is not particularly limited, and may be spherical, flaky, etc. The average particle size (50% median size on a volume basis) of the active material is preferably 5 to 100 μm, more preferably 10 to 50 μm, and even more preferably 15 to 30 μm, from the viewpoint of dispersibility of the active material. The 50% median size on a volume basis can be calculated by a laser diffraction method. The BET specific surface area of the active material is set to 0.1 to 100 m from the viewpoint of dispersibility of the active material. 2 / g, and 0.5 to 50m 2 / g is more preferable, and 1.0 to 30m 2 The BET specific surface area can be obtained by measuring the specific surface area by the BET nitrogen adsorption method (in accordance with JIS Z8830).
[0014] The positive electrode active material may be a metal composite oxide, for example, a metal composite oxide containing lithium and at least one metal selected from the group consisting of iron, cobalt, nickel, and manganese. x M y1 O2 (wherein M represents one or more transition metals, preferably at least one of Co, Mn, and Ni, and 1.10>x>0.05 and 1≧y1>0), Li x M y2 O4 (wherein M represents one or more transition metals, preferably Mn or Ni, and 1.10>x>0.05, 2≧y2>0), or Li x M y1 PO4 (wherein M represents at least one transition metal, preferably at least one of Fe, Co, Mn, and Ni, and 1.10>x>0.05, 1≧y1>0) and the like. Specific examples include LiCoO2, LiNiO2, Li x Ni y3 Mn z Co a Examples of the composite oxides include those represented by the formula: LiMn2O4, LiFePO4, and the like.
[0015] There are no particular limitations on the negative electrode active material as long as it is capable of electrochemically absorbing and releasing metal ions (for example, lithium ions), and specific examples include carbonaceous materials, metal composite oxides, and silicon compounds. As the carbonaceous material, for example, graphites such as artificial graphite and natural graphite, cokes such as petroleum coke, pitch coke, and coal coke, etc. can be used. As the metal composite oxide, for example, lithium titanate, etc. can be used. As the silicon compound, silicon, silicon oxide, etc. can be used. When these active materials are used, extremely remarkable effects can be achieved. Among these active materials, carbonaceous materials are preferred from the viewpoint of improving binding properties, particularly graphites or cokes among carbonaceous materials. Among them, it is more preferred to use graphites such as artificial graphite and natural graphite from the viewpoint of energy density per volume. In addition, among active materials other than carbonaceous materials, Li4Ti5O 12 Lithium titanate, silicon titanate, etc. are also suitable. These active materials may be used alone or in combination of two or more. The content of the active material in the non-volatile components in the slurry of the present invention is preferably 90.0 to 99.5 mass%, more preferably 95.0 to 99.0 mass%, and even more preferably 96.0 to 98.0 mass%. The non-volatile components of the slurry are the components remaining when the slurry is dried at 105°C for 1 hour in the air. The "non-volatile content of the slurry" refers to the proportion of the non-volatile components contained in the slurry.
[0016] [Binder resin (B)] The nonaqueous battery electrode slurry of the present invention contains a binder resin (B) as an essential component. The content of the binder resin (B) in the non-volatile components in the slurry of the present invention is preferably 0.5 to 5.0 mass %, more preferably 0.5 to 2.0 mass %, and even more preferably 0.5 to 1.8 mass %. The binder resin (B) used in the present invention is not particularly limited as long as it can uniformly disperse the active material (A), but is preferably a polymer of one or more ethylenically unsaturated monomers.
[0017] From the viewpoint of making the electrode formed from the slurry of the present invention less likely to crack, the binder resin (B) used in the present invention preferably has a glass transition temperature of 30° C. or less, more preferably 20° C. or less, and even more preferably 15° C. or less. From the viewpoint of handleability, the glass transition temperature of the binder resin (B) is preferably −20° C. or more.
[0018] The glass transition temperature of the binder resin (B) depends on the content of the ethylenically unsaturated monomer M used in the polymerization of the binder resin (B). i The glass transition temperature Tg of each homopolymer (i=1,2,...,i) i (i=1,2,...,i) and an ethylenically unsaturated monomer M i Each weight fraction of X i From (i=1, 2, ..., i), the theoretical value can be calculated using the following formula (I).
[0019] 1 / Tg=Σ(X i / Tg i ) ‥(I)
[0020] It is more preferable that the binder resin (B) is in a state of being dispersed in an aqueous emulsion (EM) using water as a dispersion medium, and used as a raw material for the slurry.
[0021] The aqueous emulsion (EM) of the binder resin (B) can be prepared by the following method. (1) The binder resin (B) is dispersed in water using an emulsifier and a homogenizer to prepare an aqueous emulsion (EM). (2) Using a polymerizable monomer that produces a binder resin (B) and an emulsifier, prepare an aqueous emulsion (EM) by emulsion polymerization. The binder resin (B) preferably has an acid value of 100 mgKOH / g or less, more preferably 75 mgKOH / g or less, and even more preferably 50 mgKOH / g or less. The content of the binder resin (B) in the water-based emulsion (EM), ie, the non-volatile content of the water-based emulsion (EM), is preferably from 1 to 60% by mass, more preferably from 1 to 55% by mass.
[0022] Examples of the binder resin (B) used in the present invention include copolymers (P1) of styrene-based monomers such as styrene-butadiene rubber and diene-based monomers; copolymers (P2) of styrene-based monomers and ethylenically unsaturated carboxylic acid ester monomers; and ethylene-ethylenically unsaturated carboxylic acid ester copolymers such as ethylene-vinyl acetate copolymer, ethylene-vinyl versatate copolymer, and ethylene-acrylic acid ester copolymer. Among these, the copolymers (P1) of styrene-based monomers and diene-based monomers, and the copolymers (P2) of styrene-based monomers and ethylenically unsaturated carboxylic acid ester monomers are suitable in that they can improve the binding between the active material and the binder resin (B), have excellent swelling resistance to electrolyte solvents, and are excellent in charge-discharge cycle characteristics. In addition, the copolymers (P1) of styrene-based monomers and diene-based monomers, and the copolymers (P2) of styrene-based monomers and ethylenically unsaturated carboxylic acid ester monomers are also good in that they have excellent binding to the current collector.
[0023] <Copolymer of styrene monomer and diene monomer (P1)> The copolymer (P1) of a styrene-based monomer and a diene-based monomer (hereinafter, sometimes simply referred to as "copolymer (P1)") is a copolymer having structural units derived from a styrene-based monomer such as styrene, chlorostyrene, vinyltoluene, t-butylstyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, α-methylstyrene, etc., and structural units derived from a diene-based monomer such as butadiene, isoprene, etc. A copolymer of a styrene-based monomer and a diene-based monomer can be obtained, for example, by emulsion polymerization of a raw material composition containing styrene and butadiene in an aqueous solvent in the presence of an emulsifier.
[0024] In the copolymer (P1) of a styrene monomer and a diene monomer, the ratio of structural units derived from the diene monomer is preferably 30 to 95 mass%, more preferably 40 to 90 mass%, and even more preferably 50 to 70 mass%. That is, the ratio of the diene monomer contained in the production raw material of the copolymer (P1) of a styrene monomer and a diene monomer is preferably 30 to 95 mass% or more, more preferably 40 to 90 mass%, and even more preferably 50 to 70 mass%. The ratio of structural units derived from the styrene-based monomer in the copolymer (P1) of a styrene-based monomer and a diene-based monomer is preferably 5 to 70 mass%, more preferably 10 to 60 mass%. That is, the ratio of the styrene-based monomer contained in the production raw material of the copolymer (P1) of a styrene-based monomer and a diene-based monomer is preferably 5 to 70 mass%, more preferably 10 to 60 mass%.
[0025] In order to obtain a copolymer (P1) of a styrene-based monomer and a diene-based monomer, the styrene-based monomer and the diene-based monomer can be copolymerized with other copolymerizable ethylenically unsaturated monomers such as an ethylenically unsaturated carboxylic acid monomer.
[0026] Other copolymerizable ethylenically unsaturated monomers include ethylenically unsaturated nitrile compounds such as acrylonitrile and methacrylonitrile; ethylenically unsaturated carboxylic acids such as (meth)acrylic acid; ethylenically unsaturated carboxylic acid esters such as methyl methacrylate; olefins such as ethylene and propylene; halogen atom-containing monomers such as vinyl chloride and vinylidene chloride; vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; vinyl ketones such as methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, hexyl vinyl ketone, and isopropenyl vinyl ketone; and heterocycle-containing vinyl compounds such as N-vinyl pyrrolidone, vinyl pyridine, and vinyl imidazole.
[0027] <Copolymer of styrene monomer and ethylenically unsaturated carboxylate monomer (P2)> The copolymer (P2) of a styrene-based monomer and an ethylenically unsaturated carboxylate monomer (hereinafter sometimes simply referred to as "copolymer (P2)") has a structure derived from a styrene-based monomer and a structure derived from an ethylenically unsaturated carboxylate monomer. The copolymer (P2) can be obtained, for example, by emulsion polymerization of a raw material composition containing a styrene-based monomer and an ethylenically unsaturated carboxylate monomer in an aqueous solvent in the presence of an emulsifier.
[0028] The styrene monomer mainly serves to improve the adhesion between the active material and the resin, and between the electrode active material layer and the current collector, and this effect is particularly pronounced when artificial graphite is used as the active material. The amount of the styrene-based monomer used is preferably 10 to 75 mass %, more preferably 30 to 60 mass %, and even more preferably 35 to 55 mass %, of the total ethylenically unsaturated monomer components forming the copolymer (P2). By using a styrene monomer in an amount of 10% by mass or more, the adhesion between the active material and the resin, and between the electrode active material layer and the current collector, is improved. Also, by using a styrene monomer in an amount of 70% by mass or less, the electrode formed from the composition of the present invention is less likely to break (cracks are less likely to occur). Examples of the styrene monomer include styrene, chlorostyrene, vinyltoluene, t-butylstyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, α-methylstyrene, etc. Among them, from the viewpoint of dispersibility of the active material, preferred is styrene or vinyltoluene, more preferred is styrene.
[0029] The ethylenically unsaturated carboxylic acid ester monomer may or may not have a functional group. Examples of ethylenically unsaturated carboxylate monomers having no functional group include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isononyl (meth)acrylate, isobornyl (meth)acrylate, and benzyl (meth)acrylate.
[0030] Examples of the ethylenically unsaturated carboxylate monomer having a functional group include ethylenically unsaturated carboxylate monomers having a hydroxy group, a glycidyl group, etc. Specific examples include 2-hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate, and glycidyl acrylate. Among these, from the viewpoints of ease of emulsion polymerization and durability, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, isobornyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate are preferred.
[0031] The amount of the ethylenically unsaturated carboxylic acid ester monomer used is preferably 25 to 90 mass %, more preferably 30 to 65 mass %, and even more preferably 40 to 55 mass %, of the total ethylenically unsaturated monomer components forming the above copolymer (P2). By using an ethylenically unsaturated carboxylic acid ester monomer in an amount of 25 mass % or more, the flexibility and heat resistance of the formed electrode can be improved, and by using an amount of 90 mass % or less, the adhesion between the active material and the resin, and the adhesion between the active material layer and the current collector can be improved.
[0032] An ethylenically unsaturated carboxylic acid monomer may also be used as a monomer for forming the copolymer (P2). Examples of the ethylenically unsaturated carboxylic acid monomer include unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid, and half esters of these unsaturated dicarboxylic acids, and among these, acrylic acid and itaconic acid are preferred. These ethylenically unsaturated carboxylic acid monomers may be used alone or in combination of two or more.
[0033] The amount of the ethylenically unsaturated carboxylic acid monomer used is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 8% by mass or less, and even more preferably 0.1% by mass or more and 7% by mass or less, based on the total ethylenically unsaturated monomer components forming the copolymer (P2). If the amount of the ethylenically unsaturated carboxylic acid monomer is 0.01% by mass or more, emulsion polymerization stability and mechanical stability are improved. If the amount is 10% by mass or less, the binding strength between the active material and the resin, and the binding strength between the active material layer and the current collector are good. In addition, it is preferable from the viewpoint of production stability that the acid value of the copolymer (P2) is within the above range.
[0034] As a monomer for forming the copolymer (P2), a monomer having at least one polymerizable ethylenically unsaturated group other than the above may be used. Examples of such a monomer include (meth)acrylamide, N-methylol (meth)acrylamide, (meth)acrylonitrile, vinyl acetate, vinyl propionate, and other compounds other than ethylenically unsaturated carboxylate monomers having functional groups such as amide groups and nitrile groups, sodium p-styrenesulfonate, and the like.
[0035] The raw material composition of the copolymer (P2) of a styrene-based monomer and an ethylenically unsaturated carboxylic acid ester monomer may further contain an internal crosslinking agent (internal crosslinking monomer) in order to further improve the swelling resistance of the dried film to the electrolyte solvent.
[0036] As the internal crosslinking agent, a compound having at least one ethylenically unsaturated bond and a reactive group reactive with the functional group of the above-mentioned monomer, or a compound having two or more ethylenically unsaturated bonds can be used.
[0037] Examples of such internal crosslinking agents include crosslinkable polyfunctional monomers having two or more unsaturated groups, such as divinylbenzene, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and triallyl cyanurate, and silane coupling agents having at least one ethylenically unsaturated bond, such as vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryoxypropyltrimethoxysilane, and γ-methacryoxypropyltriethoxysilane. Among these, divinylbenzene, trimethylolpropane tri(meth)acrylate, and γ-methacryoxypropyltrimethoxysilane are preferred. These internal crosslinking agents may be used alone or in combination of two or more.
[0038] The amount of the internal crosslinking agent used is preferably 0.01 to 5 mass % of the total ethylenically unsaturated monomer components forming the copolymer (P2), more preferably 0.01 to 4 mass %, and even more preferably 0.01 to 3 mass %. By setting the amount of the internal crosslinking agent to 0.01 mass % or more, it is possible to easily improve the swelling resistance of the dried film in the electrolyte, and by setting it to 5 mass % or less, it is possible to prevent a decrease in emulsion polymerization stability.
[0039] Furthermore, as a monomer for forming the copolymer (P2), a reactive emulsifier, which will be described later, may be further used.
[0040] <Emulsifier> As the emulsifier used in the emulsion polymerization, a conventional anionic emulsifier or nonionic emulsifier is used. Examples of anionic emulsifiers include alkylbenzenesulfonates, alkyl sulfates, polyoxyethylene alkyl ether sulfates, fatty acid salts, etc. Examples of nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polycyclic phenyl ethers, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, etc. These may be used alone or in combination of two or more. In addition, the use of a reactive emulsifier as the emulsifier is preferable in that it prevents the emulsifier from bleeding out and improves the mechanical stability of the electrode formed from the composition of the present invention. Examples of reactive emulsifiers include those represented by the following general formulas (1) to (5).
[0041] [ka] In the formula, R represents an alkyl group, and m represents an integer of 10 to 40.
[0042] [ka] In the formula, n is an integer of 10 to 12, and m is an integer of 10 to 40.
[0043] [ka] In the formula, R represents an alkyl group and M represents NH4 or Na.
[0044] [ka] In the formula, R represents an alkyl group.
[0045] [ka] In the formula, A is an alkylene oxide having 2 or 3 carbon atoms, and m is an integer of 10 to 40.
[0046] The suitable amount of the emulsifier is preferably 0.1 to 3.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, and even more preferably 0.2 to 1.0 parts by mass, based on 100 parts by mass of the total ethylenically unsaturated monomer components forming the copolymer, in the case of a non-reactive emulsifier. In the case of a reactive emulsifier, the amount is preferably 0.3 to 5.0% by mass, more preferably 0.5 to 4.0% by mass, and even more preferably 0.5 to 2.0% by mass, based on the total ethylenically unsaturated monomer components forming the copolymer (including the reactive emulsifier). The non-reactive emulsifier and the reactive emulsifier may be used alone, but it is preferable to use them in a mixture.
[0047] <Initiator> The radical polymerization initiator used in emulsion polymerization may be a known, commonly used one, such as ammonium persulfate, potassium persulfate, hydrogen peroxide, t-butyl hydroperoxide, etc. If necessary, these polymerization initiators may be used in combination with a reducing agent such as sodium bisulfite, Rongalit (sodium hydroxymethanesulfinate), ascorbic acid, etc. to carry out redox polymerization.
[0048] In order to adjust the molecular weight of the copolymer (P2), mercaptan, thioglycolic acid and its esters, β-mercaptopropionic acid and its esters, etc. may be used during polymerization.
[0049] <Polymerization method> As the emulsion polymerization method, a polymerization method in which the monomers constituting the binder resin (B) are charged all at once, a method in which each component is polymerized while being continuously fed, and the like are applied. The polymerization is usually carried out at a temperature of 30 to 90°C under stirring. The polymerization stability, mechanical stability, and chemical stability during emulsion polymerization can be improved by adding a basic substance during or after the polymerization of the copolymer to adjust the pH. The basic substance used in this case can be ammonia, triethylamine, ethanolamine, caustic soda, etc. These may be used alone or in combination of two or more. The pH of the adjusted aqueous emulsion (EM) is preferably 2.5 to 8.0, more preferably 5 to 7.
[0050] [Crack prevention agent (C)] The slurry of the present invention contains a crack inhibitor (C) having a boiling point of 120° C. or more at 1 atmospheric pressure and a solubility in water of 10 g / 100 mL or more at 20° C. The crack inhibitor (C) is preferably an organic solvent, and the boiling point is preferably 150° C. or more, more preferably more than 200° C. The solubility in water at 20° C. is preferably 20 g / 100 mL or more, more preferably 50 g / 100 mL or more. It is believed that by using the crack prevention agent (C) with a boiling point of 120° C. or higher, the electrode active material layer can be gradually formed while mitigating stress that is likely to cause cracks when drying the slurry. By having a solubility in water of 10 g / 100 mL or more at 20°C, the crack prevention agent (C) has high solubility in water and high hydrophilicity, and is therefore unlikely to be absorbed into the active material (A) which constitutes the majority of the slurry, thereby enabling the fluidity of the slurry to be maintained. In addition, in the present invention, it was found that the higher the boiling point of the organic solvent, the better the binding between the active materials and between the active material and the current collector. Although the details are unclear, high-boiling-point solvents, which have a large difference in boiling point from water, are less likely to take water with them when evaporated in the drying process. It is believed that the binder can be dried while being uniformly attached to the active material, since the position of the binder is less likely to change due to hydrogen bonding caused by the water being taken up. The crack inhibitor (C) is not particularly limited as long as it satisfies the boiling point and solubility. Specific examples include N-methylpyrrolidin-2-one (boiling point 202°C, miscible in water), ethylene glycol (boiling point 197°C, miscible in water), diethylene glycol (boiling point 244°C, miscible in water), ethylene glycol monobutyl ether (boiling point 171°C, miscible in water), 3-methoxy-3-methyl-1-butanol (boiling point 174°C, miscible in water), N,N-dimethylformamide (boiling point 153°C, miscible in water), and dimethyl sulfoxide (boiling point 189°C, solubility in water at 25°C of 25.3g / 100mL). Among them, N-methylpyrrolidin-2-one is particularly preferred because it has a particularly high water solubility and a high boiling point.
[0051] The content of the crack prevention agent (C) is preferably 10 to 500 parts by mass, more preferably 20 to 400 parts by mass, even more preferably 30 to 300 parts by mass, and particularly preferably 100 to 200 parts by mass, relative to 100 parts by mass of the binder resin (B).
[0052] The crack inhibitor (C) is preferably contained in an amount of 0.1 to 20.0 parts by mass, more preferably 0.3 to 10.0 parts by mass, and even more preferably 0.5 to 5.0 parts by mass, based on 100 parts by mass of the non-volatile components of the slurry.
[0053] The slurry of the present invention contains the crack inhibitor (C) in an amount of preferably 0.01 to 10 mass %, more preferably 0.10 to 5.0 mass %, and even more preferably 0.20 to 3.00 mass %.
[0054] When forming an electrode by the method described below, it is preferable that the amount of the crack prevention agent (C) contained in the slurry of the present invention remaining in the electrode is small. The amount of the black prevention agent (C) remaining in the electrode is preferably 0.05 mass% or less, more preferably 0.01 mass% or less. [Thickener (D)] The slurry of the present invention may further contain a thickener, etc., as necessary. Examples of the thickener that can be used include carboxymethylcellulose (CMC), methylcellulose, hydroxymethylcellulose, ethylcellulose, polyvinyl alcohol, polyacrylic acid, oxidized starch, phosphorylated starch, casein, and salts thereof, gum arabic, xanthan gum, alginic acid compounds, etc. These may be used alone or in combination of two or more. The amount of the thickener is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass, and further preferably 0.8 to 3.0% by mass, based on the total amount of non-volatile components of the slurry. [Slurry dispersion medium] The slurry dispersion medium of the present invention is water. It may be pure water or ion-exchanged water. The water may be a dispersion medium produced by aqueous emulsion polymerization of the binder resin (B) and used as is. The slurry may contain a dispersion medium other than water. However, the crack inhibitor (C) is not included in the dispersion medium. Examples of other dispersion mediums include alcohols such as methanol, ethanol, isopropyl alcohol, and ketones such as acetone. When using other dispersion mediums, the content of water is preferably 80% by mass or more of the total dispersion medium.
[0055] [Other additives] A conductive assistant may be added to the slurry of the present invention. The conductive assistant may be any material that has electrical conductivity between active materials. Examples of the conductive assistant include carbon black such as acetylene black, polymer carbon, and carbon fiber.
[0056] (Method for preparing slurry for non-aqueous battery electrodes) One embodiment of the method for preparing a slurry of the present invention includes, for example, a method including the following steps. (I) A step of dispersing, dissolving or kneading the binder resin (B) in a solvent. (II) A step of adding the active material (A) and any additives used as necessary, and further dispersing, dissolving or kneading the mixture. The crack inhibitor (C), the thickener (D) and other additives can be mixed in either step (I) or step (II).
[0057] Another embodiment of the method for preparing a slurry of the present invention includes, for example, a method including the following steps. (I) A step of emulsion-polymerizing the one or more ethylenically unsaturated monomers to obtain an aqueous emulsion (EM) of the binder resin (B). (II) A step of adding the active material (A) and any additives used as required to the aqueous emulsion (EM), followed by dispersing and dissolving the active material (A). The crack inhibitor (C), the thickener (D) and other additives can be mixed after step (I) or in step (II).
[0058] (Non-aqueous battery electrode) A nonaqueous battery electrode according to one embodiment of the present invention (hereinafter, may be referred to as "the electrode of this embodiment"). ) has an electrode active material layer formed on a current collector from the above-mentioned nonaqueous battery electrode slurry of the present invention. The electrode according to one embodiment of the present invention can be used as either a positive electrode or a negative electrode of a non-aqueous battery, but is particularly effective when used as a negative electrode, particularly when used as a negative electrode of a lithium ion non-aqueous battery.
[0059] The current collector in the electrode of this embodiment is not particularly limited as long as it is metallic, such as iron, copper, aluminum, nickel, stainless steel, etc. Among these, aluminum is preferable as the current collector for the positive electrode, and copper is preferable as the current collector for the negative electrode. The shape of the current collector is not particularly limited, but it is usually preferable to use a sheet-like current collector having a thickness of 0.001 to 0.5 mm.
[0060] The electrode of this embodiment has a current collector and an electrode active material layer formed on the current collector, and the electrode active material layer contains a binder resin (B) and an active material (A). The electrode active material layer is formed by curing (drying) a non-aqueous battery electrode slurry.
[0061] When the non-aqueous battery electrode of one embodiment of the present invention is a negative electrode, a negative electrode active material layer is formed on a current collector using the non-aqueous battery electrode slurry of the present invention containing the above-mentioned negative electrode active material. The amount of non-volatile components of the slurry on one side formed on the current collector (basis weight of the negative electrode active material layer) is 1 to 20 mg / cm on one side. 2 is preferable, and 5 to 20 mg / cm 2 More preferably, 10 to 15 mg / cm 2 is more preferred. When the non-aqueous battery electrode of one embodiment of the present invention is a positive electrode, a positive electrode active material layer is formed on a current collector using the slurry for a non-aqueous battery electrode of the present invention containing the above-mentioned positive electrode active material. The amount of non-volatile components of the slurry on one side formed on the current collector (basis weight of the positive electrode active material layer) is 10 to 40 mg / cm on one side. 2 is preferable, and 13 to 30 mg / cm 2 More preferably, 15 to 25 mg / cm 2 is more preferred.
[0062] In an electrode according to an embodiment of the present invention, the binder resin (B) provides good binding between active materials, and cohesive failure of the electrode active material layer can be prevented. In addition, the electrode according to this embodiment can also provide good binding between the electrode active material layer and the current collector. In particular, by using the slurry for non-aqueous battery electrodes according to the present invention, an electrode that is less susceptible to cracking can be obtained even if the slurry is applied thickly and the electrode active material layer is formed thick. This makes it possible to achieve a high energy density for non-aqueous batteries. Such an effect can be achieved extremely well, particularly when copper is used as the current collector.
[0063] [Non-aqueous battery] The nonaqueous battery according to one embodiment of the present invention is a lithium ion nonaqueous battery (hereinafter, may be referred to as the "battery according to this embodiment"). The battery according to this embodiment is constructed using the nonaqueous battery electrode according to one embodiment of the present invention described above. That is, the battery uses an electrode that is less susceptible to cracking, in which a thick electrode active material layer is formed using the slurry for nonaqueous battery electrodes according to the present invention. For example, the nonaqueous battery of this embodiment has a total thickness of 10 to 40 mg / cm 2 and the negative electrode active material layer preferably contains the above negative electrode active material layer having a density of 20 to 30 mg / cm 2 It is more preferable that:
[0064] The battery of this embodiment can be manufactured according to a known method using a positive electrode, a negative electrode, an electrolyte, and, if necessary, components such as a separator. As the electrodes, the above-mentioned electrodes of the present invention may be used for both the positive electrode and the negative electrode, or the above-mentioned electrode of this embodiment may be used for either the positive electrode or the negative electrode, but the battery is particularly effective when the above-mentioned electrode of this embodiment is used for the negative electrode. The battery can be made of a metal or aluminum laminate. The battery can be in any shape, such as a coin, button, sheet, cylindrical, rectangular, or flat shape. Any known lithium salt can be used as the electrolyte in the battery electrolyte, and the electrolyte can be selected according to the type of active material. For example, LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, and lithium lower fatty acid carboxylates.
[0065] The solvent for dissolving the electrolyte is not particularly limited as long as it is a liquid that is usually used to dissolve electrolytes, and examples of the solvent include carbonate compounds such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), and vinylene carbonate (VC); lactone compounds such as γ-butyrolactone and γ-valerolactone; ether compounds such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; and dimethyl sulfoxide. Examples of the sulphonate include sulfoxide compounds such as 1,3-dioxolane and 4-methyl-1,3-dioxolane; nitrogen-containing compounds such as acetonitrile, nitromethane, formamide, and dimethylformamide; organic acid ester compounds such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and ethyl propionate; phosphoric acid triesters and diglyme compounds; triglyme compounds; sulfolane compounds such as sulfolane and methylsulfolane; oxazolidinone compounds such as 3-methyl-2-oxazolidinone; sultone compounds such as 1,3-propane sultone, 1,4-butane sultone, and naphtha sultone; and the like. These may be used alone or in combination of two or more. The non-aqueous battery of one embodiment of the present invention may be a lithium-ion non-aqueous battery.
[0066] (Method of manufacturing non-aqueous battery electrodes) A method for producing a non-aqueous battery electrode according to one embodiment of the present invention includes the following steps. (III) A step of applying the nonaqueous battery electrode slurry obtained in the steps (I) and (II) onto a current collector and drying the applied slurry to form an electrode active material layer. The electrode of this embodiment can be obtained, for example, by applying the above-mentioned slurry for a non-aqueous battery electrode of the present invention onto a current collector and drying it. The coating method can be a general method, for example, a reverse roll method, a direct roll method, a doctor blade method, a knife method, an extrusion method, a curtain method, a gravure method, a bar method, a dip method, and a squeeze method. Among these, the doctor blade method, the knife method, or the extrusion method is preferred from the viewpoint of improving the surface condition of the electrode active material layer by selecting the coating method according to the various physical properties such as the viscosity and the drying property of the slurry of the present invention. The drying temperature can be selected from 25°C to 180°C according to the various physical properties and drying property of the resin contained in the slurry, and the drying time. From the viewpoint of work efficiency, for example, 50°C to 150°C is preferred, and 60°C to 120°C is more preferred. In addition, the electrode of this embodiment can be pressed as necessary after the electrode active material layer is formed. As the pressing method, a general method can be used, but in particular, a mold pressing method or a calendar pressing method is preferable. The pressing pressure is not particularly limited, but is 0.2 to 3 t / cm. 2 is preferred. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the examples and comparative examples, "parts" and "%" respectively indicate parts by mass and % by mass unless otherwise specified. The materials used in the examples and comparative examples, as well as the slurries for non-aqueous battery electrodes and electrodes for non-aqueous batteries obtained in the examples and comparative examples, were subjected to the following measurements and evaluations. The results are shown in Tables 2 and 3.
[0068] [Evaluation method] (Non-volatile content of water-based emulsion (EM) and non-volatile content of slurry) 1 g of the aqueous emulsion (EM) or slurry was weighed as an evaluation sample onto an aluminum dish with a diameter of 5 cm, dried at 105°C for 1 hour in air, and the residue was weighed to perform the calculation.
[0069] (viscosity) The measurements were carried out using a Brookfield type rotational viscometer at a liquid temperature of 23° C., a rotation speed of 60 rpm, and a No. 2 or No. 3 rotor.
[0070] (pH) The pH (23°C) of the aqueous emulsion (EM) was measured by the glass electrode method using a pH meter (Horiba, Ltd., F-52).
[0071] (Average particle size of resin particles dispersed in water-based emulsion (EM)) The average particle size (50% median diameter on a volume basis) was measured using a UPA type particle size distribution measuring device (Microtrack Bell Co., Ltd.). (Acid value) The acid value was measured according to the potentiometric titration method of JIS K 0070 and converted into a solid content.
[0072] (Slurry appearance) The components described below were mixed to obtain a slurry for a non-aqueous battery electrode (negative electrode). After 10 minutes had passed, the slurry was visually observed. Those that showed separation or sediment in the liquid or had no fluidity were marked with an X, and those that were uniformly dispersed were marked with an O.
[0073] (Electrode appearance) After the electrodes were prepared, their surfaces were visually observed, and those with cracks were marked with "x" and those without cracks were marked with "o."
[0074] (Adhesion of electrodes) The prepared negative electrode was left at 23°C and 50% RH for 24 hours to prepare a test specimen. The peel strength between the active material layer and the current collector of the test specimen was measured based on JIS K6854-2. The slurry-coated surface of the test specimen was attached to a SUS plate using double-sided tape, and 180° peeling was performed (peel width 25 mm, peel speed 100 mm / min) to measure the peel strength. A low peel strength means that the active material layer is prone to cohesive failure and has low adhesion between the active materials and between the active material and the current collector.
[0075] [Synthesis example] (Synthesis of binder resin B-1) A separable flask equipped with a condenser, a thermometer, a stirrer, and a dropping funnel was charged with 32.6 parts by mass of ion-exchanged water, 0.11 parts by mass of a reactive anionic emulsifier represented by the above general formula (4) (manufactured by Sanyo Chemical Industries, Ltd., product name ELEMINOL JS-20, active ingredient 40% by mass), and 0.02 parts by mass of a non-reactive anionic emulsifier (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., product name Hitenol 08E, polyoxyethylene alkyl ether sulfate), and the mixture was subjected to submerged bubbling with nitrogen gas for 1 hour, after which the temperature was raised to 75°C. Next, a monomer emulsion obtained by previously mixing 0.48 parts by mass of the reactive anionic emulsifier represented by the general formula (4), 0.17 parts by mass of a non-reactive anionic emulsifier (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., trade name Hitenol 08E, polyoxyethylene alkyl ether sulfate), 49.2 parts by mass of styrene, 43.1 parts by mass of 2-ethylhexyl acrylate, 1.90 parts by mass of 2-hydroxyethyl methacrylate, 1.90 parts by mass of acrylic acid, 0.60 parts by mass of sodium parastyrenesulfonate, 0.04 parts by mass of divinylbenzene, and 67.9 parts by mass of ion-exchanged water was added dropwise over 3 hours. At the same time, a solution of 0.40 parts by mass of potassium persulfate dissolved in 9.30 parts by mass of ion-exchanged water as a polymerization initiator was added dropwise at 80°C over 3 hours to polymerize. After the dropwise addition was completed, the mixture was aged for 2 hours and then cooled, and 2.10 parts by mass of ammonia water was added to obtain an anionic water-based emulsion EM1 with binder resin B-1 dispersed therein. The obtained anionic water-based emulsion EM1 had a pH of 5.0, a viscosity of 40 mPa s, a ratio of binder resin B-1 in the water-based emulsion (non-volatile content) of 40 mass%, an average particle size of the resin particles in the emulsion of 250 nm, and the binder resin had a glass transition temperature of 15°C and an acid value of 40 mgKOH / g.
[0076] (Synthesis of binder resin B-2) Anionic water-based emulsion EM2 in which binder resin B-2 was dispersed was obtained in the same manner as water-based emulsion EM1, except that 52.4 parts by mass of styrene, 40.6 parts by mass of 2-ethylhexyl acrylate, 3.80 parts by mass of acrylic acid, 1.90 parts by mass of itaconic acid, 0.60 parts by mass of sodium parastyrenesulfonate, and 0.67 parts by mass of divinylbenzene were used as monomers. The obtained anionic water-based emulsion EM2 had a non-volatile content of 40% by mass, pH 7.0, and viscosity of 60 mPa·s, the average particle size of the resin particles in the water-based emulsion was 300 nm, and the binder resin B-2 had a glass transition temperature of 15°C and an acid value of 40 mgKOH / g.
[0077] (Binder resin B-3) As the anionic aqueous emulsion EM3 in which binder resin B-3 was dispersed, BM-400B manufactured by Zeon Corporation (styrene-butadiene rubber containing 69.8% by mass of styrene and 30% by mass of butadiene, non-volatile content of 40% by mass, pH 7.0, viscosity 11 mPa s, average particle size of resin particles in the aqueous emulsion of 190 nm, glass transition temperature -7°C, acid value 25 mg KOH / g) was prepared.
[0078] Example 1 <Preparation of negative electrode slurry> Active material (artificial graphite SCMG (registered trademark)-XRs, manufactured by Showa Denko K.K., particle diameter 12 μm, specific surface area 2.5 m 2 % aqueous solution of CMC (weight average molecular weight 3 million, degree of substitution 0.9) as a thickener (D) and water in the ratios shown in Table 1 (step 1), and then emulsion EM1 as a binder resin (B), NMP as a crack inhibitor (C) and water in the ratios shown in Table 1 (step 2) were mixed to obtain a non-aqueous battery electrode (negative electrode) slurry of Example 1. The evaluation results are shown in Table 2.
[0079] [Table 1]
[0080] (Preparation of negative electrode) The non-aqueous battery electrode (negative electrode) slurry was applied onto one side of a copper foil current collector to a wet thickness of 280 μm, dried by heating at 60° C. for 2 minutes, and then further dried at 100° C. for 2 minutes. The other side was then coated and dried in the same manner. The amount of non-volatile components in the slurry formed on one side of the current collector was 12 mg / cm. 2 , 24mg / cm on both sides 2 The evaluation results are shown in Table 2.
[0081] (Examples 2 to 10) (Comparative Examples 1 to 8) A slurry for a non-aqueous battery electrode and a non-aqueous battery electrode were obtained in the same manner as in Example 1, except that the crack inhibitor (C) and the aqueous emulsion (EM) as the binder resin (B) were changed to the formulations shown in Tables 2 and 3. The evaluation results are shown in Tables 2 and 3. The crack inhibitors used are as follows: NMP: N-methylpyrrolidin-2-one (Wako Pure Chemical Industries, Ltd.) Butyl cellosolve: Ethylene glycol monobutyl ether (manufactured by Dow Chemical Japan Co., Ltd.) EG: Ethylene glycol (manufactured by Maruzen Petrochemical Co., Ltd.) DEG: Diethylene glycol (Wako Pure Chemical Industries, Ltd.) DMF: N,N-dimethylformamide (Wako Pure Chemical Industries, Ltd.) DMSO: Dimethyl sulfoxide (Wako Pure Chemical Industries, Ltd.) Solfit: 3-methoxy-3-methyl-1-butanol (Kuraray Co., Ltd.) IPA: Isopropyl alcohol (Tokuyama Corporation) n-Butanol: 1-butanol (Mitsubishi Chemical Corporation) Benzyl alcohol: Benzyl alcohol (Ark Co., Ltd.) Phenoxyethanol-SP: Phenoxyethanol (manufactured by Yokkaichi Chemical Co., Ltd.) Wigenol EHP01: Propylene glycol mono-2-ethylhexanoate (manufactured by Yokkaichi Chemical Co., Ltd.) Texanol: 2,2,4-trimethyl-1,3-pentanediol 2-methylpropanoate (manufactured by Chisso Corporation) Benzoflex 9-88: Dipropylene glycol dibenzoate (Velsicol Chemical)
[0082] [Table 2]
[0083] [Table 3]
[0084] (Examples 11 to 12) (Comparative Examples 9 to 10) A slurry for a non-aqueous battery electrode and a non-aqueous battery electrode were obtained in the same manner as in Example 1 and Comparative Example 1, except that the crack inhibitor (C) and the aqueous emulsion (EM) were changed to the formulations shown in Tables 2 and 3. The evaluation results are shown in Tables 2 and 3.
[0085] As is clear from the evaluation results of the slurries for nonaqueous battery electrodes and the evaluation results of the nonaqueous battery electrodes prepared using the same shown in Tables 2 and 3, in Examples 1 to 12 in which the slurries for nonaqueous battery electrodes of the present invention were used, the electrodes did not crack and had high adhesion to the electrodes. Among them, Examples 1 to 4, 7, 11, and 12 in which a crack prevention agent having a boiling point of over 200° C. was used had particularly excellent electrode adhesion.
Claims
1. A non-aqueous battery electrode active material (A); A binder resin (B), A crack inhibitor (C); Water and A non-aqueous battery electrode slurry comprising: The crack inhibitor (C) has a boiling point of 120° C. or higher at 1 atmospheric pressure and a solubility in water of 10 g / 100 mL or higher at 20° C., The content of the crack inhibitor (C) is 10 to 200 parts by mass relative to 100 parts by mass of the binder resin (B), The binder resin (B) is at least one selected from the group consisting of a copolymer (P1) of a styrene-based monomer and a diene-based monomer, and a copolymer (P2) of a styrene-based monomer and an ethylenically unsaturated carboxylic acid ester monomer.
2. The non-aqueous battery electrode slurry according to claim 1, wherein the crack inhibitor (C) is at least one selected from N-methylpyrrolidin-2-one, ethylene glycol, diethylene glycol, ethylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, N,N-dimethylformamide, and dimethyl sulfoxide.
3. 2. The slurry for a non-aqueous battery electrode according to claim 1, wherein the crack inhibitor (C) is an organic solvent having a boiling point of 150° C. or higher at 1 atmospheric pressure.
4. The slurry for a non-aqueous battery electrode according to claim 1 , wherein the crack inhibitor (C) is an organic solvent having a boiling point of more than 200° C. at 1 atmospheric pressure.
5. The slurry for a non-aqueous battery electrode according to any one of claims 1 to 4, further comprising a thickener (D).
6. 6. The non-aqueous battery electrode slurry according to claim 5, wherein the thickener (D) is carboxymethyl cellulose (CMC).
7. The slurry for a non-aqueous battery electrode according to any one of claims 1 to 6, wherein the binder resin (B) contains a copolymer (P1) of a styrene-based monomer and a diene-based monomer, and the styrene-based monomer component is 5 to 70 mass% of the total ethylenically unsaturated monomer components constituting the copolymer, and the diene-based monomer component is 30 to 95 mass%.
8. The non-aqueous battery electrode slurry according to any one of claims 1 to 6, wherein the binder resin (B) contains a copolymer (P2) of a styrene-based monomer and an ethylenically unsaturated carboxylic acid ester monomer.
9. The slurry for a non-aqueous battery electrode according to any one of claims 1 to 6, wherein the binder resin (B) comprises a copolymer of a styrene-based monomer, an ethylenically unsaturated carboxylic acid ester monomer, and an ethylenically unsaturated carboxylic acid monomer.
10. the amount of styrene used in the binder resin (B) is 10 to 70 mass % of the total ethylenically unsaturated monomer components forming the copolymer, the amount of the ethylenically unsaturated carboxylic acid ester monomer used is 25 to 85% by mass of the total ethylenically unsaturated monomer components forming the copolymer, The slurry for a non-aqueous battery electrode according to claim 9, wherein the amount of the ethylenically unsaturated carboxylic acid monomer used is 0.01 to 10 mass% of the total ethylenically unsaturated monomer components forming the copolymer.
11. A method for producing a non-aqueous battery electrode, comprising the steps of applying the slurry according to any one of claims 1 to 10 onto a current collector and drying the applied slurry.
12. A method for producing a non-aqueous battery, comprising the method for producing a non-aqueous battery electrode according to claim 11.
Citation Information
Patent Citations
Secondary battery negative electrode
JP1993074461A
Aqueous binder for forming battery electrode
JP1996250123A
Binder for battery binder solution, electrode mixture, electrode structure and battery
JP1998298386A
Binder resin composition, mix slurry, electrode, and nonaqueous electrolyte secondary battery using these
JP2004210980A
Lithium secondary battery
JP2006278104A